2022
DOI: 10.21203/rs.3.rs-1584090/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental study on anti-freezing and thawing performance of basalt fiber reinforced fly ash concrete under corrosive conditions

Abstract: Basalt fiber reinforced fly ash concrete (BFRFAC) is a new inorganic non-metal composite building material with superior mechanical performance, which can be extensively applied in the fields of bridge floors, pavements and other construction engineering projects. In the present paper, the freezing and thawing resistance performance of BFRFAC under corrosion conditions was studied in detail with the comparison to the Normal Concrete (NC). Experimental studies on the mass loss rate (MLR) in a non-corrosive envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…4) BF had the strong resistance of acid and alkali corrosion, it not undergo significant changes due to the corrosion of the salt solution in the concrete, so it could continue to play a positive role in supporting the framework and connecting bonds in the corrosive environment. The surrounding concrete was tightly wrapped together by BF, which slowed down the change process of concrete from dense to loose, slowed down the decrease of relative dynamic elastic modulus during the freeze-thaw cycle of concrete, and enhanced the ability of concrete to resist freeze-thaw damage (Jin et al, 2015).…”
Section: Frost Resistancementioning
confidence: 99%
“…4) BF had the strong resistance of acid and alkali corrosion, it not undergo significant changes due to the corrosion of the salt solution in the concrete, so it could continue to play a positive role in supporting the framework and connecting bonds in the corrosive environment. The surrounding concrete was tightly wrapped together by BF, which slowed down the change process of concrete from dense to loose, slowed down the decrease of relative dynamic elastic modulus during the freeze-thaw cycle of concrete, and enhanced the ability of concrete to resist freeze-thaw damage (Jin et al, 2015).…”
Section: Frost Resistancementioning
confidence: 99%
“…Professor Mehta [1] has pointed out that the freeze-thaw cycle is one of the main reasons for the reduction of concrete durability. In northeast and northwest of China, a large number of concrete structures are damaged due to long-term freeze-thaw cycles of varying degrees, seriously affecting the service life and safety performance of concrete structures, and causing certain economic losses [2,3]. Therefore, improving the frost resistance of concrete material is helpful to improve the durability of concrete structures.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al in their research studies on BFRC found that basalt fiber could improve the splitting tensile and flexural strength of concrete, but it had a delayed effect on the early compressive strength of concrete [10]. In the area of frost, basalt fiber significantly enhanced freeze thaw resistance and durability of concrete under corrosion conditions [11]. Authors in [12] claimed that basalt fiber was able to improve the impact resistance number and performance of BFRC.…”
Section: Introductionmentioning
confidence: 99%